Operation of police equipment on duty under martial law - T. V. Shevchenko; F. F. Zurov; P. M. Frolenkova (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the problematic issues of operation of police equipment during the service of ensuring public security and order under the legal regime of martial law, shows the current state of modern research on the topic, and outlines the main problems faced by police officers when operating equipment. The publications on this topic are reviewed, and the regulatory framework of the MIA of Ukraine on the analysed issue is also studied.